O Perfil das contribuições científicas internacionais sobre Green Supply Chain Management - Araújo, Andreza Rodrigues de (Universidade Federal Rural do Semi-Árido, 2018)
The present study maps the scientific contributions published in international journals in the area of Production Management and Green Operations, for the theme "Green Supply Chain Management". To do so, it makes use of bibliometrics (author network, quantitative of articles published by journals x years, quantitative articles published by theoretical perspective x year, quantitative of articles published by type of research x analysis technique and collection procedures) and identifies methodological aspects (unit of analysis, collection procedure and collection technique) of the articles available in the base of ScienceDirect, from January 2011 to April 2018, which resulted in a sample composed by 45 (forty five) articles. With the collection and analysis of data of each article, it was verified that the theme had an emphasis in the year 2015 (17), caused mainly by the publications in the journal entitled "Procedia - Social and Behavioral Sciences" (16). Among the authors who establish a greater number of relationships with other researchers, we highlight Galankashi (6) and Acquaye (5). Regarding the theoretical perspective, the studies that draw the most attention are those that deal with performance measurement (14) and Green strategy (10). Among the most common types of research, those with a quantitative character (38) and the use of the matrix or super matrix technique (8) were more present. The use of bibliographic research (27) and the questionnaire (11) predominates when it comes to collection procedures, which is understandable in theoretical discussions (26).
Monografia
Keywords: Bibliometria; Administração da Produção; Operações Verdes; Green supply chain management; Bibliometrics; Production Management; Green Operations; Green supply chain management; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO